Insulin‐like growth factor I and risk of incident cancer in elderly men – results from MrOS (Osteoporotic Fractures in Men) in Sweden. (19th November 2015) - Carlzon, Daniel; Svensson, Johan; Petzold, Max; Karlsson, Magnus K.; Ljunggren, Östen; Haghsheno, Mohammad‐Ali; Damber, Jan‐Erik; Mellström, Dan; Ohlsson, Claes
Summary: Objective: Studies of the association between circulating IGF‐I and cancer risk have shown conflicting results. We have previously observed a U‐shaped association between IGF‐I and cancer mortality. This study test the hypotheses of a U‐shaped association between IGF‐I and incident cancer. Design: Elderly men (2368), randomly recruited from the general community. Methods: IGF‐I was measured in a cohort of elderly men. Complete data for incident cancer were obtained from the Swedish Cancer Registry. Statistical analyses included Cox proportional hazards regressions with or without a spline approach. Results: Three hundred and sixty‐nine participants had incident cancer after baseline. Prostate cancer was most frequent ( n = 140). There was no association between serum IGF‐I and all cancer or prostate cancer incidence. However, there was a nonlinear association between IGF‐I and nonprostate cancer incidence ( P = < 0·05). Exploratory analyses were performed for low and high serum IGF‐I (quintiles 1 and 5) vs intermediate (quintiles 2–4, referent). There was a tendency of increased nonprostate cancer risk in men with high IGF‐I (HR = 1·26, 95% confidence interval (CI): 0·92–1·71, P = 0·15). After excluding participants with follow‐up of less than 2·6 years (half median follow‐up time), to control for potential diagnostic delay, the association was statistically significant (HR = 1·55, CI: 1·03–2·35). Conclusion: There was a significant nonlinear association between IGF‐I and nonprostate cancer. No association between IGF‐I and prostate cancer was observed. Future studies are warranted to further investigate this nonlinear association, including whether IGF‐I concentration is a reproducible, and useful, risk marker of nonprostate cancer.